AB0161 A MMP1-cleavable composite peptide derived from BIG-H3 potently inhibits chronic inflammatory arthritis. (23rd January 2014) - Kang, J.H.; Nam, E.J.; Sa, K.H.; Kim, K.H.; Seo, J.S.; Han, S.W.; Kang, Y.M.
Abstract : Background: Transforming growth factor β-inducible gene-h3 (βig-h3), an extracellular matrix protein, is composed of four homologous fas-1 domains and an RGD motif. We previously demonstrated that βig-h3 was abundantly expressed in rheumatoid synovium and regulated the adhesion and migration of fibroblast-like synoviocytes (FLS), which was inhibited by the YH18 peptide in the 4th fas-1 domain (4th YH18 peptide). Objectives: To develop βig-h3 derivative-based peptides that have a therapeutic efficacy in chronic inflammatory arthritis. Methods: The βig-h3 derivative-based peptides, including the 2nd and 4th YH peptides, 4th fas-1 domain, 4th fas-1 truncated for H1 and H2 (dhfas-1), and a MMP1-cleavable composite peptide (MFK24), were cloned. We tested the MFK24 with different proteases and confirmed the specificity of cleavage by immunoblotting with anti-βig-h3 and anti-His-tag antibodies. Inhibitory effect of adhesion and migration of FLS or mouse fibroblast (NIH3T3) was evaluated in 96-well microtiter and transwell plates coated with βig-h3. A murine collagen-induced arthritis (CIA) model was used for evaluation of therapeutic efficacy of the βig-h3 derivative-based peptides. Results: The 4th YH18 peptide was weakly effective in suppressing the arthritis severity in CIA mice. The human and murine (MFK00) dhfas-1 was effective in blocking the βig-h3-mediated adhesion and migration of human FLS and murine fibroblasts. Treatment with higher dose (30mg/kg) of dhfas-1 showed a remarkable efficacy, whereas treatment with lower dose (10 mg/kg) revealed only a partial improvement. A composite peptide (MFK24) consisted of dhfas-1 and RGD peptide linked by MMP1 substrate was cleaved by MMP1 specifically. βig-h3-mediated adhesion and migration of NIH3T3 cells were inhibited at low concentration (0.5 and 1 uM respectively) of MFK24. MFK24 suppressed the adhesion of NIH3T cells more efficiently compared to either alone in combination of MFK00 and RGD motif. Therapeutic efficacy of MFK24 in CIA mice was remarkably enhanced with a consistent reduction of expression in inflammatory mediators within joint tissues. Conclusions: A proof of concept design of the MMP-cleavable composite peptide, based on βig-h3 derivatives, revealed a marked exaltation of therapeutic efficacy for chronic inflammatory arthritis, implicating a new expandable strategy for enhancement of efficacy of two different active molecules in the treatment of RA. Disclosure of Interest: None Declared